2021
DOI: 10.3390/nano11082111
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Superplasticity and Strengthening in CoNiCrFeMn High Entropy Alloy Nanowires Using Atomistic Simulations

Abstract: High strength and ductility, often mutually exclusive properties of a structural material, are also responsible for damage tolerance. At low temperatures, due to high surface energy, single element metallic nanowires such as Ag usually transform into a more preferred phase via nucleation and propagation of partial dislocation through the nanowire, enabling superplasticity. In high entropy alloy (HEA) CoNiCrFeMn nanowires, the motion of the partial dislocation is hindered by the friction due to difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Tripathi et al discovered that chemical fluctuations in CoNiCrFeMn HEA NWs facilitate the formation of nucleation sites for FCC-HCP MT. 380 At elevated temperature, the dominance of MT in these HEA nanowires enhances ductility and flow stress. Furthermore, Ruestes and Farkas simulated the tensile deformation of a Fe−Ni−Cr−Co−Cu NW, revealing that dislocations emitted from the free surface govern its mechanical behavior.…”
Section: Bulk Nanostructured Heasmentioning
confidence: 99%
See 1 more Smart Citation
“…Tripathi et al discovered that chemical fluctuations in CoNiCrFeMn HEA NWs facilitate the formation of nucleation sites for FCC-HCP MT. 380 At elevated temperature, the dominance of MT in these HEA nanowires enhances ductility and flow stress. Furthermore, Ruestes and Farkas simulated the tensile deformation of a Fe−Ni−Cr−Co−Cu NW, revealing that dislocations emitted from the free surface govern its mechanical behavior.…”
Section: Bulk Nanostructured Heasmentioning
confidence: 99%
“…The plastic deformation in these nanowires is accommodated by reversible FCC-HCP martensitic transformations (MT), which offer lower energy barriers compared to deformation twinning pathways (Figure b). Tripathi et al discovered that chemical fluctuations in CoNiCr­FeMn HEA NWs facilitate the formation of nucleation sites for FCC-HCP MT . At elevated temperature, the dominance of MT in these HEA nanowires enhances ductility and flow stress.…”
Section: Nanosized Heasmentioning
confidence: 99%
“…High-entropy alloys (HEAs) and multiprincipal element alloys have received considerable interest for community experts and have become a worldwide hot spot since Cantor and Yeh reported their first publication [1,2]. Cr-containing HEAs have exhibited promising potential when applied in high-temperature industrial fields as a result of their remarkable strength [3][4][5][6], favorable ductility [7][8][9], distinguished corrosion resistance [10][11][12], superior wear and oxidation resistance [13][14][15], and acceptable thermal stability [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The shape memory effects are attributed to the reversible transition from FCC to HCP phase. As the temperature rises from 77 K to 1000 K, the plastic deformation mechanism changes from twinning to phase transition, which means that the CoN-iCrFeMn HEA NWs still maintain good plasticity at high temperatures [54]. Ruestes et al [55] found that compared with average atomic materials, the peak stress of FeCoNiCrCu HEA NWs was lower, and the flow stress was higher.…”
Section: Introductionmentioning
confidence: 99%